A kind of impermeable concrete and its preparation process
Through the modification of nanosilicon dioxide and composite fibers, the problem of reduced hydration ability caused by the hydrophilicity of nanosilicon dioxide in concrete is solved, and the resistance to seepage, cracking and freeze-thaw resistance is significantly improved.
Patent Information
- Application Number
- CN202211733533.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The nanosilicon dioxide in existing impermeable concrete has strong hydrophilicity, which causes its moisture absorption to weaken the hydration ability of the concrete and reduces the impermeable resistance.
The nano-silica is modified by using silane coupling agent to change its surface from hydrophilicity to hydrophobicity, and combined with modified polyvinyl alcohol fibers and glass fibers and composite fibers of steel fibers to enhance the impermeability of concrete. Resistant to cracking and freeze-thaw resistance.
Through the use of modified nano silica and composite fibers, the concrete's permeability resistance is significantly improved, moisture migration and early shrinkage crack formation are reduced, and the concrete's compactness and freeze-thaw resistance are enhanced.
Smart Images

Figure BDA0004032417740000091 
Figure BDA0004032417740000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of concrete, and in particular to an anti-seepage concrete and a preparation process thereof. Background Art
[0002] Concrete is a non-homogeneous material composed of gel material, aggregate, admixture, water, etc. Due to its strong bearing capacity and abundant raw material sources, concrete can be made into building components of different strengths, properties and shapes. It is the most widely used building material in various building structures. As concrete structures are exposed to adverse environments for a long time, their performance gradually decreases. Therefore, admixtures are often added to concrete to improve its performance.
[0003] For related technology, reference may be made to the Chinese invention patent application with publication number CN112390579A, which discloses an impermeable concrete and a preparation process thereof. The impermeable concrete comprises the following components in parts by mass: 100 parts of cement, 30-50 parts of water, 120-150 parts of sand, 280-310 parts of crushed stone, 1-3 parts of water reducer, 5-7 parts of nano-silicon dioxide, 60-75 parts of rubber particles, and 50-64 parts of granite powder; the impermeability of the concrete can be effectively improved.
[0004] With regard to the above-mentioned related technologies, the inventors believe that there are the following defects: since there are a large number of hydroxyl groups on the surface of nano-silica and it is highly hydrophilic, as the amount of nano-silica added increases, the excessively large specific surface area of nano-silica will absorb more water, thereby weakening the hydration ability of cement and causing the concrete's impermeability to decrease. Summary of the invention
[0005] In order to improve the anti-seepage ability of concrete, the present application provides an anti-seepage concrete and a preparation process thereof.
[0006] The present application provides an anti-seepage concrete, which adopts the following technical solution:
[0007] The invention discloses an impermeable concrete and a preparation process thereof. The raw materials include, by weight, 380-460 parts of cement, 120-200 parts of fly ash, 650-800 parts of sand, 1000-1200 parts of stone, 10-20 parts of water reducer, 50-70 parts of expansion agent, 50-65 parts of modified nano silicon dioxide, 12-20 parts of composite fiber and 140-200 parts of water. The modified nano silicon dioxide includes the following components: 58-70 parts of nano silicon dioxide, 12-18 parts of silane coupling agent, 2-5 parts of sodium silicate and 180-240 parts of deionized water.
[0008] By adopting the above technical solution and modifying nano-silica with a silane coupling agent, the hydrophilicity of nano-silica can be changed to hydrophobicity, thereby improving the effect of nano-silica on the anti-seepage performance of concrete. This is because the silane coupling agent can react with the hydroxyl groups on the surface of nano-silica after hydrolysis, so that the original hydrophilic surface of nano-silica rich in hydroxyl groups is changed into a hydrophobic surface containing organic functional groups, thereby preventing nano-silica from absorbing more water, reducing the influence of the hydrophilicity of nano-silica on the hydration capacity of concrete, and thus improving the anti-seepage capacity of concrete.
[0009] Preferably, the composite fiber comprises modified polyvinyl alcohol fiber, glass fiber and steel fiber in a weight ratio of 1:(0.6-1.2):(0.3-0.6).
[0010] By adopting the above technical solution, using composite fibers of polyvinyl alcohol fiber, glass fiber, and steel fiber, the anti-permeability performance of concrete can be improved. This is because the fiber can reduce the formation and expansion of early shrinkage cracks in concrete, thereby reducing the porosity inside the concrete. In addition, after adding fibers to concrete, the migration of water between the various gaps can be reduced, and the number of capillaries formed due to water loss can be reduced, thereby achieving the effect of reducing capillary tension, thereby improving the anti-permeability performance of concrete.
[0011] Preferably, the modified polyvinyl alcohol fiber comprises the following components: 36-48 parts of polyvinyl alcohol fiber, 1.7-3.5 parts of dioctyl adipate, 3-5 parts of silane coupling agent, 45-68 parts of ethanol, 1-3 parts of sodium persulfate, 12-18 parts of alkyl acid polyoxyethylene ether, 35-49 parts of deionized water, and 7-13 parts of polyethylene glycol.
[0012] By adopting the above technical scheme, modified polyvinyl alcohol fiber is used to improve the effect of composite fiber on improving the anti-permeability performance of concrete. Polyvinyl alcohol fiber is used as reinforcing fiber of concrete, has good affinity and bonding with cement, can produce great internal restriction on expansion, make concrete more compact, can inhibit shrinkage cracks during cement hardening, and enhance the bending toughness of concrete. However, polyvinyl alcohol has a large moisture absorption rate and will absorb moisture in concrete. Therefore, it is hydrophobic modified by silane coupling agent to reduce its water absorption capacity. At the same time, by compounding dioctyl adipate, the toughness and cold resistance of polyvinyl alcohol fiber can be increased, thereby improving the improvement effect of composite fiber on the anti-permeability and anti-freeze-thaw ability of concrete.
[0013] Preferably, the silane coupling agent is silane coupling agent KH-550.
[0014] By adopting the above technical solution, the silane coupling agent KH-550 is used to perform hydrophobic modification on nano-silicon dioxide and polyvinyl alcohol fibers, so that the water absorption capacity of the nano-silicon dioxide and polyvinyl alcohol fibers can be reduced.
[0015] The present application also provides a process for preparing impermeable concrete, which adopts the following technical solution:
[0016] A process for preparing impermeable concrete comprises the following steps:
[0017] 380-460 parts of cement, 120-200 parts of fly ash, 650-800 parts of sand, 1000-1200 parts of stone, 10-20 parts of water reducer, 50-70 parts of expansion agent, 50-65 parts of modified nano silicon dioxide, 12-20 parts of composite fiber and 140-200 parts of water are mixed and stirred evenly to obtain impermeable concrete.
[0018] By adopting the above technical solution, modified nano-silicon dioxide and composite fibers are used as admixtures in concrete, which is not only beneficial to improving the anti-permeability of concrete, but also beneficial to improving the crack resistance and freeze-thaw resistance of concrete.
[0019] Preferably, the preparation method of the modified nano-silicon dioxide comprises the following steps:
[0020] Add 58-70 parts of nano-silicon dioxide and 12-18 parts of silane coupling agent to 180-240 parts of deionized water, mix well and adjust the pH to 3.5-4.5, increase the temperature and react for 5-8 hours, wash with deionized water after the reaction is completed, filter and dry to obtain modified nano-silicon dioxide; place the modified silicon dioxide in a blender, add 2-5 parts of sodium silicate, and stir to disperse.
[0021] By adopting the above technical solution and modifying the nano-silica with a silane coupling agent, the hydrophilicity of the nano-silica can be changed to hydrophobicity, thereby improving the effect of the nano-silica on the anti-seepage performance of concrete.
[0022] Preferably, the method for preparing the composite fiber comprises the following steps:
[0023] Modified polyvinyl alcohol fiber, glass fiber and steel fiber are weighed in a weight ratio of 1: (0.6-1.2): (0.3-0.6), 1-1.5 parts of dispersant are added to each of them and mixed, and then the short fibers of each of them are obtained by crushing, sieving, acid washing and drying. After the short fibers of the three are mixed, 2-3 parts of reinforcing agent are added and stirred to obtain the composite fiber.
[0024] By adopting the above technical solution and using composite fibers, through the compounding of polyvinyl alcohol fiber, glass fiber and steel fiber, they stimulate and complement each other at different scales and performance levels, effectively improving the concrete's impermeability, crack resistance and freeze-thaw resistance.
[0025] Preferably, the method for preparing the modified polyvinyl alcohol fiber comprises the following steps:
[0026] S1. 36-48 parts of polyvinyl alcohol fiber were added to the acetic acid solution for impregnation, and after the impregnation was completed, the fiber was rinsed with deionized water until the rinse solution was neutral, and then dried to obtain pretreated polyvinyl alcohol fiber;
[0027] S2. 1.7-3.5 parts of dioctyl adipate and 3-5 parts of a silane coupling agent are dissolved in 45-68 parts of ethanol to obtain a mixed solution A, 1-3 parts of sodium persulfate and 12-18 parts of alkyl acid polyoxyethylene ether are added to 35-49 parts of deionized water, mixed well, and then the mixed solution A and 2-5 parts of polyethylene glycol are added and heated, and mixed well to obtain a solution B;
[0028] S3. Melt solution B to obtain a molten liquid, add the polyvinyl alcohol fibers pretreated in S1 and 5-8 parts of polyethylene glycol to the molten liquid and mix them evenly, take out and wash with water, dry and obtain modified polyvinyl alcohol fibers.
[0029] By adopting the above technical scheme, the polyvinyl alcohol fiber is hydrophobically modified by using a silane coupling agent, so that its water absorption capacity can be reduced. At the same time, by compounding dioctyl adipate, the toughness and cold resistance of the polyvinyl alcohol fiber can be increased, thereby improving the composite fiber's effect on the concrete's impermeability and freeze-thaw resistance.
[0030] In summary, the present application includes at least one of the following beneficial technical effects:
[0031] 1. By adopting the above technical solution, the silane coupling agent is used to modify the nano-silicon dioxide, so that the hydrophilicity of the nano-silicon dioxide can be changed to hydrophobicity, thereby improving the effect of the nano-silicon dioxide on the anti-seepage performance of concrete. This is because the silane coupling agent can react with the hydroxyl groups on the surface of the nano-silicon dioxide after hydrolysis, so that the original hydrophilic surface of the nano-silicon dioxide rich in hydroxyl groups is changed into a hydrophobic surface containing organic functional groups, thereby preventing the nano-silicon dioxide from absorbing more water, reducing the influence of the hydrophilicity of the nano-silicon dioxide on the hydration ability of the concrete, thereby improving the anti-seepage ability of the concrete;
[0032] 2. By adopting the above technical solution, the composite fiber of polyvinyl alcohol fiber, glass fiber and steel fiber can improve the anti-permeability of concrete. This is because the fiber can reduce the formation and expansion of early shrinkage cracks in concrete, thereby reducing the porosity inside the concrete. In addition, after adding the fiber to the concrete, the migration of water between the gaps can be reduced, and the number of capillaries formed due to water loss can be reduced, thereby achieving the effect of reducing capillary tension, thereby improving the anti-permeability of concrete; 3. By adopting the above technical solution, the modified polyvinyl alcohol fiber can be used to improve the anti-permeability of concrete by the composite fiber. Function: Polyvinyl alcohol fiber is used as reinforcing fiber of concrete. It has good affinity and bonding with cement, can produce great internal restrictions on expansion, make concrete more compact, inhibit shrinkage cracks during cement hardening, and enhance the bending toughness of concrete. However, polyvinyl alcohol has a large moisture absorption rate and will absorb moisture in concrete. Therefore, it is hydrophobically modified by silane coupling agent to reduce its water absorption capacity. At the same time, by compounding with dioctyl adipate, the toughness and cold resistance of polyvinyl alcohol fiber can be increased, thereby improving the composite fiber's effect on the concrete's impermeability and freeze-thaw resistance. DETAILED DESCRIPTION
[0033] The present application is further described in detail below with reference to the embodiments.
[0034] Preparation Example
[0035] Preparation Example Ⅰ Preparation of modified nano-silicon dioxide
[0036] Preparation Example I-1
[0037] 58g of nano-silica and 12g of silane coupling agent KH-550 were added to 180g of deionized water, and ultrasonically mixed for 60min at a temperature of 40°C and an ultrasonic frequency of 60kHz to obtain a mixed solution, and the pH value was adjusted to 3.5 with a 30% hydrochloric acid solution, and the mixture was reacted for 8h at a temperature of 70°C. After the reaction was completed, the mixture was filtered and washed with deionized water until the washing liquid was neutral, and dried at a temperature of 130°C for 1h to obtain modified nano-silica.
[0038] Preparation Example I-2
[0039] 64g of nano-silica and 15g of silane coupling agent KH-550 were added to 210g of deionized water, and ultrasonically mixed for 70min at a temperature of 50°C and an ultrasonic frequency of 65kHz to obtain a mixed solution, and the pH value was adjusted to 4 with a 30% hydrochloric acid solution, and the temperature was increased to 75°C and reacted for 6.5h. After the reaction was completed, deionized water was used for suction filtration and washing until the washing liquid was neutral, and dried at a temperature of 110°C for 2h to obtain modified nano-silica.
[0040] Preparation Example I-3
[0041] 70g of nano-silica and 18g of silane coupling agent KH-550 were added to 140g of deionized water, and ultrasonically mixed for 80min at a temperature of 60°C and an ultrasonic frequency of 70kHz to obtain a mixed solution, and the pH value was adjusted to 4.5 with a 30% hydrochloric acid solution by mass fraction, and the temperature was increased to 80°C and reacted for 5h. After the reaction was completed, deionized water was used for suction filtration and washing until the pH value of the washing liquid reached 7, and the solution was dried at a temperature of 120°C for 1.5h to obtain modified nano-silica.
[0042] Preparation Example II Preparation of modified polyvinyl alcohol fiber
[0043] Preparation Example II-1
[0044] S1. 36 g of polyvinyl alcohol fiber was added to a 25% mass fraction acetic acid solution, and immersed at a temperature of 25° C. and an ultrasonic frequency of 40 kHz for 2 h. After the immersion, the fiber was rinsed with deionized water until the pH of the rinse solution reached 7, and dried at 130° C. for 1.5 h to obtain the pretreated polyvinyl alcohol fiber;
[0045] S2. 1.7 g of dioctyl adipate and 3 g of silane coupling agent were dissolved in 45 g of ethanol, mixed at a temperature of 35 ° C and an ultrasonic frequency of 60 kHz for 45 min to obtain a mixed solution A, 1 g of sodium persulfate and 12 g of alkyl acid polyoxyethylene ether were added to 35 g of deionized water, mixed at a temperature of 35 ° C and an ultrasonic frequency of 60 kHz for 45 min, and after mixing evenly, the mixed solution A and 2 g of polyethylene glycol were added, the temperature was raised to 65 ° C, and mixed at 80 kHz for 2 h to obtain a solution B;
[0046] S3. Solution B is melted at a temperature of 200°C to obtain a molten liquid, and the polyvinyl alcohol fiber pretreated in S1 and 5 g of polyethylene glycol are added to the molten liquid, and stirred at a temperature of 78°C and a rotation speed of 3000 rpm for 4 hours. After taking out, it is washed with water and dried at 110°C for 1 hour to obtain modified polyvinyl alcohol fiber.
[0047] Preparation Example II-2
[0048] S1. 42 g of polyvinyl alcohol fiber was added to a 25% mass fraction acetic acid solution, and immersed at a temperature of 30° C. and an ultrasonic frequency of 45 kHz for 3 h. After the immersion, the fiber was rinsed with deionized water until the pH of the rinse solution reached 7, and dried at 120° C. for 2 h to obtain the pretreated polyvinyl alcohol fiber;
[0049] S2. 2.6 g of dioctyl adipate and 4 g of silane coupling agent were dissolved in 56 g of ethanol, mixed at a temperature of 40 ° C and an ultrasonic frequency of 65 kHz for 50 min to obtain a mixed solution A, 2 g of sodium persulfate and 15 g of alkyl acid polyoxyethylene ether were added to 42 g of deionized water, mixed at a temperature of 40 ° C and an ultrasonic frequency of 65 kHz for 50 min, and after uniform mixing, the mixed solution A and 3.5 g of polyethylene glycol were added, the temperature was raised to 70 ° C, and mixed at 85 kHz for 2.5 h to obtain a solution B;
[0050] S3. Solution B is melted at a temperature of 220°C to obtain a molten liquid, and the polyvinyl alcohol fiber pretreated in S1 and 6.5 g of polyethylene glycol are added to the molten liquid, and stirred at a temperature of 85°C and a rotation speed of 3500 rpm for 4.5 hours. After taking out, it is washed with water and dried at 120°C for 1.5 hours to obtain modified polyvinyl alcohol fiber.
[0051] Preparation Example II-3
[0052] S1. 48 g of polyvinyl alcohol fiber was added to a 25% mass fraction acetic acid solution, and immersed at a temperature of 35 ° C and an ultrasonic frequency of 50 kHz for 2.5 hours. After the immersion, it was rinsed with deionized water until the pH of the rinse solution reached 7, and dried at 110 ° C for 3 hours to obtain the pretreated polyvinyl alcohol fiber;
[0053] S2. 3.5 g of dioctyl adipate and 5 g of silane coupling agent were dissolved in 68 g of ethanol, mixed at a temperature of 45 ° C and an ultrasonic frequency of 70 kHz for 55 min to obtain a mixed solution A, 3 g of sodium persulfate and 18 g of alkyl acid polyoxyethylene ether were added to 49 g of deionized water, mixed at a temperature of 45 ° C and an ultrasonic frequency of 70 kHz for 55 min, and after mixing, the mixed solution A and 5 g of polyethylene glycol were added, the temperature was raised to 75 ° C, and mixed at 90 kHz for 3 h to obtain a solution B;
[0054] S3. Solution B is melted at a temperature of 235°C to obtain a molten liquid, and the polyvinyl alcohol fiber pretreated in S1 and 8 g of polyethylene glycol are added to the molten liquid, and stirred at a temperature of 95°C and a rotation speed of 4000 rpm for 5 hours. After taking out, it is washed with water and dried at 130°C for 2 hours to obtain modified polyvinyl alcohol fiber.
[0055] Example
[0056] Example 1
[0057] S1. The modified nano-silica obtained in Preparation Example Ⅰ-1 was placed in a blender, 2 g of sodium silicate was added, and the mixture was stirred and dispersed to obtain a modified nano-silica powder;
[0058] S2. Weigh 10g of the modified polyvinyl alcohol fiber obtained in Preparation Example Ⅱ-1, 6g of glass fiber, and 3g of steel fiber, add 1g of dispersant to each of them, mix them, crush the fibers, pass them through a 300-mesh sieve, and then wash them with 10% dilute hydrochloric acid, and dry them at 120°C for 2h to obtain their respective short fibers; after mixing the short fibers of the three, add 2g of reinforcing agent, stir for 25s, and obtain composite fibers. The dispersant used in this embodiment is calcium carbonate, and the reinforcing agent used is barium sulfate;
[0059] S3. 380g cement, 120g fly ash, 650g sand, 1000g stone, 10g water reducer, 50g expansion agent, 50g modified nano-silicon dioxide powder obtained by S1, 12g composite fiber obtained by S2, and 140g water are mixed and stirred to obtain impermeable concrete. The water reducer used in this embodiment is a naphthalene-based high-efficiency water reducer, the main component of which is a naphthalenesulfonate formaldehyde condensate; the expansion agent used is a CSA expansion agent, the main component of which is anhydrous calcium sulphoaluminate.
[0060] Example 2
[0061] S1. The modified nano-silica obtained in Preparation Example Ⅰ-1 was placed in a blender, 3.5 g of sodium silicate was added, and the mixture was stirred and dispersed to obtain a modified nano-silica powder;
[0062] S2. Weigh 10g of the modified polyvinyl alcohol fiber obtained in Preparation Example Ⅱ-1, 6g of glass fiber, and 3g of steel fiber, add 1.3g of dispersant to each of them, mix them, crush the fibers, pass them through a 400-mesh sieve, wash them with 10% dilute hydrochloric acid, and dry them at 130°C for 2.5h to obtain their respective short fibers; mix the short fibers of the three, add 2.5g of reinforcing agent, stir for 30s, and obtain composite fibers. The dispersant used in this embodiment is calcium carbonate, and the reinforcing agent used is barium sulfate;
[0063] S3. 420g cement, 160g fly ash, 725g sand, 1100g stone, 15g water reducer, 60g expansion agent, 50g modified nano-silicon dioxide powder obtained by S1, 12g composite fiber obtained by S2, and 170g water are mixed and stirred to obtain impermeable concrete. The water reducer used in this embodiment is a naphthalene-based high-efficiency water reducer, the main component of which is a naphthalenesulfonate formaldehyde condensate; the expansion agent used is a CSA expansion agent, the main component of which is anhydrous calcium sulphoaluminate.
[0064] Example 3
[0065] S1. The modified nano-silica obtained in Preparation Example Ⅰ-1 was placed in a blender, 5 g of sodium silicate was added, and the mixture was stirred and dispersed to obtain a modified nano-silica powder;
[0066] S2. Weigh 10g of the modified polyvinyl alcohol fiber obtained in Preparation Example Ⅱ-1, 6g of glass fiber, and 3g of steel fiber, add 1.5g of dispersant to each of them, mix them, crush the fibers, pass them through a 500-mesh sieve, and then wash them with 10% dilute hydrochloric acid, and dry them at 140°C for 1.5h to obtain their respective short fibers; after mixing the short fibers of the three, add 3g of reinforcing agent, stir for 35s, and obtain composite fibers. The dispersant used in this embodiment is calcium carbonate, and the reinforcing agent used is barium sulfate;
[0067] S3. 460g cement, 200g fly ash, 800g sand, 1200g stone, 20g water reducer, 70g expansion agent, 50g modified nano-silicon dioxide powder obtained by S1, 12g composite fiber obtained by S2, and 200g water are mixed and stirred to obtain impermeable concrete. The water reducer used in this embodiment is a naphthalene-based high-efficiency water reducer, the main component of which is a naphthalenesulfonate formaldehyde condensate; the expansion agent used is a CSA expansion agent, the main component of which is anhydrous calcium sulphoaluminate.
[0068] Example 4
[0069] The difference between Example 4 and Example 1 is that the modified nano-silica used in S1 of Example 4 comes from Preparation Example I-2.
[0070] Example 5
[0071] The difference between Example 5 and Example 1 is that the modified nano-silica used in S1 of Example 5 comes from Preparation Example I-3.
[0072] Example 6
[0073] The difference between Example 6 and Example 1 is that the mass of the modified nano-silicon dioxide powder used in S3 of Example 6 is 57 g.
[0074] Example 7
[0075] The difference between Example 7 and Example 1 is that the mass of the modified nano-silicon dioxide powder used in S3 of Example 7 is 65 g.
[0076] Example 8
[0077] The difference between Example 8 and Example 1 is that the modified polyvinyl alcohol fiber used in S2 of Example 8 comes from Preparation Example II-2.
[0078] Example 9
[0079] The difference between Example 9 and Example 1 is that the modified polyvinyl alcohol fiber used in S2 of Example 9 comes from Preparation Example II-3.
[0080] Example 10
[0081] The difference between Example 10 and Example 1 is that in Example 10, the mass of the modified polyvinyl alcohol fiber used in S2 is 10 g, the mass of the glass fiber is 9 g, and the mass of the steel fiber is 4.5 g.
[0082] Embodiment 11
[0083] The difference between Example 11 and Example 1 is that in Example 11, the mass of the modified polyvinyl alcohol fiber used in S2 is 10 g, the mass of the glass fiber is 12 g, and the mass of the steel fiber is 6 g.
[0084] Example 12
[0085] The difference between Example 12 and Example 1 is that the mass of the composite fiber used in S3 of Example 12 is 16 g.
[0086] Example 13
[0087] The difference between Example 13 and Example 1 is that the mass of the composite fiber used in S3 of Example 13 is 20 g.
[0088] Comparative Example
[0089] Comparative Example 1
[0090] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, unmodified common nano-silicon dioxide is used in S1.
[0091] Comparative Example 2
[0092] The difference between Comparative Example 2 and Example 1 is that the mass of the modified nano-silicon dioxide powder used in S3 of Comparative Example 2 is 40 g.
[0093] Comparative Example 3
[0094] The difference between Comparative Example 3 and Example 1 is that the mass of the modified nano-silicon dioxide powder used in S3 of Comparative Example 3 is 75 g.
[0095] Comparative Example 4
[0096] The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, unmodified common polyvinyl alcohol fiber is used in S2.
[0097] Comparative Example 5
[0098] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, the mass of the modified polyvinyl alcohol fiber used in S2 is 10 g, the mass of the glass fiber is 3 g, and the mass of the steel fiber is 2 g.
[0099] Comparative Example 6
[0100] The difference between Comparative Example 6 and Example 1 is that in Comparative Example 6, the mass of the modified polyvinyl alcohol fiber used in S2 is 10 g, the mass of the glass fiber is 16 g, and the mass of the steel fiber is 10 g.
[0101] Comparative Example 7
[0102] The difference between Comparative Example 7 and Example 1 is that the mass of the composite fiber used in S3 of Comparative Example 7 is 8 g.
[0103] Comparative Example 8
[0104] The difference between Comparative Example 8 and Example 1 is that the mass of the composite fiber used in S3 of Comparative Example 8 is 25 g.
[0105] Performance testing
[0106] 1. Test the water penetration depth of the standard test block using the step-by-step pressure method in accordance with GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete".
[0107] 2. Test the anti-seepage pressure of standard test blocks in accordance with GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete".
[0108] 3. According to GB / T 50081-2016 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", standard test blocks are made, and the number of cracks per unit area and the total cracking area per unit area are calculated 24 hours after concrete pouring.
[0109] 4. The antifreeze performance is measured in accordance with GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" and characterized by antifreeze grades. The maximum number of freeze-thaw cycles at which the relative dynamic elastic modulus drops to 60% of the initial value or the mass loss rate reaches 5% is used as the concrete antifreeze grade, represented by the symbol F. Concrete with an antifreeze grade ≥ F50 is called antifreeze concrete.
[0110] The specific test results are shown in Table 1:
[0111] Table 1 Performance test results of concrete obtained from Examples 1-13 and Comparative Examples 1-8
[0112]
[0113]
[0114] It can be seen from the data in Table 1 that the water seepage depth of the impermeable concrete provided by the present application is ≤3.8 mm; the water seepage pressure can reach 4.9 MPa, and the number of cracks per unit area is ≤7.8 / m 2, the total cracking area per unit area is ≤110, and the maximum number of freeze-thaw cycles can reach 440 times. It can be seen that the impermeable concrete provided by the present application has strong impermeability, crack resistance and freeze-thaw resistance.
[0115] It can be seen from the test results of Examples 1-3 that the process parameters for preparing impermeable concrete provided in the present application are all beneficial to improving the impermeability, crack resistance and freeze-thaw resistance of concrete.
[0116] It can be seen from the test results of Examples 1, 4, 5 and Comparative Example 1 that the modified nano-silica provided in the present application is more conducive to improving the impermeability, crack resistance and freeze-thaw resistance of concrete than unmodified ordinary nano-silica.
[0117] It can be seen from the test results of Examples 1, 6, 7 and Comparative Examples 2 and 3 that when the mass of the modified nano-silica provided by the present application increases, the water seepage depth of the concrete gradually decreases, the anti-seepage pressure gradually increases, the number of cracks per unit area and the total crack area per unit area are slightly reduced, and the anti-freeze ability is slightly increased. However, when the mass of the modified nano-silica exceeds 65g, the anti-seepage ability, crack resistance and freeze-thaw resistance of the concrete begin to decrease again.
[0118] It can be seen from the test results of Examples 1, 8, 9 and Comparative Example 4 that the modified polyvinyl alcohol fiber provided in the present application is more conducive to improving the impermeability, crack resistance and freeze-thaw resistance of concrete than the unmodified ordinary polyvinyl alcohol fiber.
[0119] It can be seen from the test results of Examples 1, 10, 11 and Comparative Examples 5 and 6 that when the weight ratio of the composite fiber provided by the present application, the modified polyvinyl alcohol fiber, the glass fiber, and the steel fiber varies in the range of 1: (0.6-1.2): (0.3-0.6), the obtained concrete water seepage depth, anti-seepage pressure, number of cracks per unit area, total cracked area per unit area, and anti-freeze ability data do not change much, but when the weight ratio of the modified polyvinyl alcohol fiber, the glass fiber, and the steel fiber is lower than or exceeds the range of 1: (0.6-1.2): (0.3-0.6), the concrete's anti-seepage ability, crack resistance, and freeze-thaw resistance are significantly reduced.
[0120] It can be seen from the test results of Examples 1, 12, 13 and Comparative Examples 7 and 8 that when the mass of the composite fiber provided in the present application increases, the water seepage depth of the concrete gradually decreases, the anti-seepage pressure gradually increases, the number of cracks per unit area and the total crack area per unit area both decrease slightly, and the anti-freeze ability increases slightly. However, when the mass of the composite fiber exceeds 25g, the anti-seepage ability, crack resistance and freeze-thaw resistance of the concrete begin to decrease again.
[0121] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An impermeable concrete, characterized in that: The raw materials include, by weight: 380-460 parts of cement, 120-200 parts of fly ash, 650-800 parts of sand, 1000-1200 parts of stone, 10-20 parts of water reducer, 50-70 parts of expansion agent, 50-65 parts of modified nano-silicon dioxide, 12-20 parts of composite fiber, and 140-200 parts of water; The modified nano silicon dioxide comprises the following components: 58-70 parts of nano silicon dioxide, 12-18 parts of silane coupling agent, 2-5 parts of sodium silicate, and 180-240 parts of deionized water; The preparation method of the modified nano silicon dioxide comprises the following steps: Add 58-70 parts of nano-silicon dioxide and 12-18 parts of silane coupling agent to 180-240 parts of deionized water, mix well and adjust the pH to 3.5-4.5, raise the temperature to react for 5-8 hours, wash with deionized water after the reaction is completed, filter and dry to obtain modified nano-silicon dioxide; place the modified silicon dioxide in a mixer, add 2-5 parts of sodium silicate, and stir to disperse; The composite fiber includes modified polyvinyl alcohol fiber, glass fiber, and steel fiber in a weight ratio of 1: (0.6-1.2): (0.3-0.6); The method for preparing the composite fiber comprises the following steps: The modified polyvinyl alcohol fiber, glass fiber and steel fiber are weighed in a weight ratio of 1: (0.6-1.2): (0.3-0.6), 1-1.5 parts of dispersant are added to each fiber and mixed, and then the fibers are crushed, sieved, acid-washed and dried to obtain short fibers of each fiber. After the short fibers of the three fibers are mixed, 2-3 parts of reinforcing agent are added and stirred to obtain the composite fiber. The modified polyvinyl alcohol fiber comprises the following components: 36-48 parts of polyvinyl alcohol fiber, 1.7-3.5 parts of dioctyl adipate, 3-5 parts of silane coupling agent, 45-68 parts of ethanol, 1-3 parts of sodium persulfate, 12-18 parts of alkyl acid polyoxyethylene ether, 35-49 parts of deionized water, and 7-13 parts of polyethylene glycol; The preparation method of the modified polyvinyl alcohol fiber comprises the following steps: S1. 36-48 parts of polyvinyl alcohol fiber were added to the acetic acid solution for impregnation, and after the impregnation was completed, the fiber was rinsed with deionized water until the rinse solution was neutral, and then dried to obtain pretreated polyvinyl alcohol fiber; S2. 1.7-3.5 parts of dioctyl adipate and 3-5 parts of a silane coupling agent are dissolved in 45-68 parts of ethanol to obtain a mixed solution A, 1-3 parts of sodium persulfate and 12-18 parts of alkyl acid polyoxyethylene ether are added to 35-49 parts of deionized water, mixed well, and then the mixed solution A and 2-5 parts of polyethylene glycol are added and heated, and mixed well to obtain a solution B; S3. Melt solution B to obtain a molten liquid, add the polyvinyl alcohol fibers pretreated in S1 and 5-8 parts of polyethylene glycol to the molten liquid and mix them evenly, take out and wash with water, dry and obtain modified polyvinyl alcohol fibers.
2. The impermeable concrete according to claim 1, characterized in that: The silane coupling agent is silane coupling agent KH-550.
3. A process for preparing an impermeable concrete according to claim 1 or 2, characterized in that: The following steps are involved: 380-460 parts of cement, 120-200 parts of fly ash, 650-800 parts of sand, 1000-1200 parts of stone, 10-20 parts of water reducer, 50-70 parts of expansion agent, 50-65 parts of modified nano silicon dioxide, 12-20 parts of composite fiber and 140-200 parts of water are mixed and stirred evenly to obtain impermeable concrete.
Citation Information
Patent Citations
Impermeable concrete and preparation method thereof
CN112390579A
High-toughness hybrid fiber reinforced concrete and a preparing method thereof
CN106242429A
Preparation method of fiber-reinforced cement based composite material with high toughness and high damping
CN106431131A
Siliceous anti-cracking compacted waterproof agent for mortar concrete and preparation method thereof
CN108793796A
Corrosion-resistant polymer cement coating and preparation method thereof
CN114836084A